Innovation in the Malaysian Traditional Food Industry: A Conceptual Paper - Abdullah, Khairunnisa Mohamad; Putit, Lennora; Yulia, Cica (Advances in Social Sciences Research Journal, 2024)
Nowadays, Malaysia ‘s sub-sector of the agricultural commodity industry, particularly the innovative and convenient traditional food products, is expanding in tandem with increasing urbanisation and women workforce, reduction in household size and current lifestyle changes respectively. There are a variety of products in the Malaysian market that have been created by incorporating innovation into traditional Malaysian foods. As such, this situation has led to intense competition and oversupply of products in the market, and it requires food companies to develop critical strategies for introducing innovations in traditional foods so as to be sustainable and more competitive. The aim of this paper is two-fold: firstly, to provide an overview of innovation development in the Malaysian traditional food industry. This paper reveals that, studies on innovation in Malaysian traditional food industry remains under-researched and scarce until to date. The present study also reveals that a clear understanding of consumer perceptions, needs, and preferences, as well as a product's quality attributes, is critical when making even minor changes to traditional foods, thus leading to successful introduction of innovation in traditional foods. Besides that, sustaining consumer continuance behaviour beyond initial purchase and consumption is crucial for innovative food product success and sustained market.